Michelangelo : the young artist who dreamed of perfection - Wilkinson, Philip (Washington, D.C. : National Geographic, 2006)
An illustrated biography of Renaissance sculptor and painter Michelangelo that describes the world in which he lived and such artistic accomplishments as the statue of David and the ceiling of the Sistine Chapel.
Includes bibliographical references (p. 62) and index.
6.7
3-6
3-6
Wilson's Children
Wilson's Junior High School
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Artists -- Italy -- Biography -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Artists; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography